Recomendações para avaliação da experiência de usuário em aplicativos móveis para surdos - Guimarães, Ana Paula Nunes (2014)
The use of mobile devices brings great benefits of connectivity to its users. However, access to information through these devices is a new challenge of interaction for users who have some kind of disability. Currently, most mobile applications have accessibility barriers that make it difficult or impossible the usage for many individuals with special needs. To ensure access to the content to all users regardless of their health status, this paper proposes a model for evaluating user interfaces accessibility focused on mobile devices. The proposed model takes into account the users experience without neglecting the specificities of mobile context and accessibility scenario. As a result, there is a group of perceptions observed from the tests performed to evaluate the three mobile applications developed for deaf. As a contribution, there is a group of recommendations for the evaluation of the user experience and the challenges and new perspectives to evaluate the mobile accessibility, given that few methods consider these two contexts in a coupled way.